Reversible unfolding of cytochrome c upon interaction with cardiolipin bilayers. 1. Evidence from deuterium NMR measurements. - Spooner, P; Watts, A (1991)
Deuterium NMR has been used to investigate the structure and dynamic state of cytochrome c complexed with bilayers of cardiolipin. Reductive methylation was employed to prepare [N epsilon, N epsilon-C2H3]lysyl cytochrome c, and deuterium exchange provided labeling of backbone sites to give [amide-2H]cytochrome c or more selective labeling of just histidine residues in [epsilon-2H]histidine cytochrome c. Deuterium NMR measurements on [N epsilon, N epsilon-C2H3]lysyl cytochrome c in the solid state showed restricted motions, fairly typical of the behavior of aliphatic side-chain sites in proteins. The [amide-2H]cytochrome c provided "immobile" amide spectra showing that only the most stable backbone sites remained labeled in this derivative. Relaxation measurements on the aqueous solution of [amide-2H]cytochrome c yielded a rotational correlation time of 7.9 ns for the protein, equivalent to a hydrodynamic diameter of 4.0 nm, just 0.6 nm greater than its largest crystallographic dimension. Similar measurements on [epsilon-2H]histidine cytochrome c in solution showed that all labeled histidine residues were also "immobile" compared with the overall reorientational motion of the protein. The interaction with cardiolipin bilayers appeared to create a high degree of mobility for the side-chain sites of [N epsilon, N epsilon-C2H3]lysyl cytochrome c and perturbed backbone structure to instantaneously release all deuterons in [amide-2H]cytochrome c. The [epsilon-2H]histidine cytochrome c derivative, when complexed with cardiolipin, failed to produce any detectable wide-line 2H NMR spectrum, demonstrating that the overall reorientational motion of bound protein was not isotropic on the NMR time scale, i.e., tau c greater than 10(-7)s.(ABSTRACT TRUNCATED AT 250 WORDS)